A Qualitative Study on Emotions Experienced at the Coast and Their Influence on Well-Being - Severin, Marine I.; Raes, Filip; Notebaert, Evie; Lambrecht, Luka; Everaert, Gert; Buysse, Ann (Frontiers in Psychology, 2022)
Coastal environments are increasingly shown to have a positive effect on our health and well-being. Various mechanisms have been suggested to explain this effect. However, so far little focus has been devoted to emotions that might be relevant in this context, especially for people who are directly or indirectly exposed to the coast on a daily basis. Our preregistered qualitative study explored how coastal residents experience the emotions they feel at the coast and how they interpret the effect these emotions have on them. We conducted semi-structured interviews with a purposive sample of eight Belgian coastal residents aged 21–25 years old. The interviews were analyzed with the approach of interpretative phenomenological analysis. Five superordinate themes were identified and indicate that, for our participants, the coast represents a safe haven (1) in which they can experience emotional restoration (2), awe (3), and nostalgia (4). These emotional states are accompanied with adaptive emotion regulating strategies (5), such as reflection and positive reappraisal, that may facilitate coping with difficult thoughts and feelings. Our study demonstrates the importance of investigating specific emotions and related processes triggered at the coast and how these could contribute to the therapeutic value of the coast.